Students’ Perception of the Use Google Translate in English Learning - Syafryadin Syafryadin; Margiana Margiana (Yayasan Karinosseff Muda Indonesia, 2023)
The purpose of this study is to ascertain how students view Google Translation as an aid for learning English. The pervasive usage of Google Translation by college students is what inspired this study. In order to better understand how students perceive using Google Translation to study English, researchers conducted research. Two research questions have been developed to address the aforementioned issues. The first is the proportion of students in the English Department who use Google Translate to learn English, and the second is how the students themselves view using Google Translate to learn English. Researchers utilize a quantitative descriptive research strategy in the interim to address defined research questions. In this study, two sets of questionnaires were utilized as the instruments: the first set was used to gather data for the first research question, and the second set was used to gather data for the second research question. Respondents to this survey were enrolled full-time in STKIP Muhammadiyah Pagar Alam's English Department for the academic year 2022–2023. They were all chosen through purposeful sampling. The results of this study show that STKIP Muhammadiyah Pagar Alam students in the English Department utilize Google Translate to learn English since they occasionally have trouble understanding it, especially while doing translation work. They make use of technology to assist them in tasks like translation, diction, checking for synonyms and antonyms, and checking pronunciation. Additionally, they have a favorable opinion of Google Translation as a tool for learning English, with the majority of their